Educational technology using multimedia in science learning: A systematic review - Riza, Lala Septem; Hasanah , Lilik Nur; Putri , Ananda Hafizhah; Budiman, Budiman; Safitri, Fibriyana; Putri , Liandha Arieska; Hayati , Nurlaila; Solihah, Putri Amelia; Samah, Khyrina Airin Fariza Abu (Association for Scientific Computing Electrical and Engineering, 2023)
This systematic review aims to provide a systematic review of the scientific published studies that examined different multimedia tools in the science teaching and learning process to identify the existing multimedia-based tools and understand their usage, application areas, and impacts on the education system. There are 60 articles extracted from the Scopus database from 2012 to 2022. This review generates six averments about the current study; (1) The most numerous multimedia components are text components; (2) the learning process and application of the use of multimedia in science education can be applied at various levels of education; (3) The majority of the study was conducted in the United States; (4) the current use of technology that is most widely used is the use of power points; (5) the role of technology in the learning process as learning tools, teaching tools, assessment, and evaluation; and (6) the most science content conducted in multimedia research is chemistry.